India for All?: Assessing the Impact of Health on Political Participation in India - Jinwon Han (Asian Journal for Public Opinion Research)
Since Narendra Modi and his Bharatiya Janata Party (BJP) assumed power with broad support in 2014, Indian politics has been undergoing a great transition, emphasizing the vision of “India for all” through inclusive growth. However, achieving and sustaining inclusive growth requires equal political participation, and yet there remains a substantial gap in citizens’ political engagement in India. Based on rational choice theory and political mobilization theory, I examined whether individuals’ health affects their political participation. Using ordinal logistic regression (OLR), I identified a significant effect of health on political participation in the Indian context. In light of the findings, I proposed several policy implications.